Relay‐Assisted Communication Over FTR/IFTR Channels - Haider Mehdi; Zakir Hussain; Muhammad Junaid Rabbani; Syed Muhammad Atif Saleem; Syed Areeb Ahmed (Engineering Reports)
ABSTRACT This work presents an analysis of decode and forward (DF) relay‐assisted device‐to‐device (D2D) communication over a novel fluctuating two‐ray (FTR) faded channel affected by co‐channel interference (CCI). CCI fading condition is assumed to follow a novel independent fluctuating two‐ray (IFTR) model. The FTR model consists of dominant components that jointly fluctuate, plus a diffuse component. The IFTR model complements the FTR model by allowing the dominant components to fluctuate independently. Both models are typically incorporated in various environments because of their generalized nature. The contributions of this paper include analyses of relay‐assisted D2D FTR/IFTR system with two cases. These cases are considered based on diversity schemes at the relay and D2D receiver: (A) Selection combining (SC) at relay and D2D receiver and (B) Maximal ratio combining (MRC) at relay and D2D receiver. Also, the expressions for outage probability, success probability and capacity with outage over Terahertz (THz) communication channels are derived by the help of characteristic function (CF). These expressions are functions of THz channel conditions, distances between various communication nodes of the system, diversity scheme parameters and various FTR/IFTR fading channel parameters. It is observed that the variation in CCI IFTR parameters slightly effect the overall performance of the D2D system. Furthermore, by increasing pointing errors of D2D signals system performance degrades. However, performance is improved when CCI pointing errors are increased.